Lightroom 5 : Streamlining Your Digital Photography Process. - Sylvan, Rob (Wiley, 2013)
Manage your images with Lightroom and this beautifully illustrated guide Image management can soak up huge amounts of a photographer's time, but help is on hand. This complete guides teaches you how to use Adobe Lightroom 5 to import, manage, edit, and showcase large quantities of images with impressive results. The authors, both professional photographers and Lightroom experts, walk you through step.